Bahasa Indonesia in UNESCO’s 43rd general conference speech: a social practice analysis - Muhammad Alim Akbar Nasir; Wilma Prafitri (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
This study examines a speech delivered by Abdul Mu'ti, Minister of Primary and Secondary Education, on behalf of the Government of Indonesia at UNESCO’s 43rd General Conference on 4 November 2025, using the social practice dimension as the analytical framework. The data consist of the official speech manuscript. The analysis relies on close analytical reading of the speech to connect language choices and statement content with institutional legitimacy, diplomatic norms, and Indonesia’s position in global governance. The findings indicate that the use of Bahasa Indonesia functions as a normal and accepted part of the UNESCO forum, not simply as a ceremonial or symbolic language act. In this context, Bahasa Indonesia is used as a practical language for official communication and is maintained across the speech’s substantive sections. The speech builds credibility by referring to education as a right, presenting enrollment figures, and naming policy programs, presenting Indonesia’s actions as aligned with global goals while keeping a formal diplomatic tone. It also places Indonesia within UNESCO-related fields beyond education, including science, the environment, culture, and communication, and follows common diplomatic routines such as expressing gratitude and showing solidarity. The closing use of an Indonesian cultural form, pantun, fits the formal setting, showing that cultural expression can be present in an international forum without undermining official authority.